Influence of different milk-clotting enzymes on the process of producing soft cheeses - D. S. Myagkonosov; I. T. Smykov; D. V. Abramov; I. N. Delitskaya; V. N. Krayushkina (Пищевые системы)
The effect of the type of milk clotting enzyme (MCE) on the duration of milk coagulation, parameters of the composition of whey and cheeses, and the output of cheeses in the production of soft cheese such as “Lyubitel'skiy” were investigated. Three brands of MCE of different origins were investigated: Marzyme® (MCE of microbial origin based on Rhizomucor miehei protease), Naturen® (calf rennet) and Chy-max® M (recombinant camel chymosin). It was established that MCEs had different ratios of milk clotting activity (MCA) to total proteolytic activity (PA). It was determined that the MCA/PA ratio, which characterizes the degree of specificity of the MCE action with regard to kappa-casein, in Chy-max M 1000 is ~7 times higher than that of Naturen and ~50 times higher than that of Marzyme. Such differences did not lead to a negative effect when using the Marzyme preparation in the production of soft cheeses. There were no statistically significant differences in the amount of dry matter loss of the curd into the whey, physicochemical parameters and output between the variants of cheeses made with the studied brands of MCE. Shorter duration of milk clotting (16.5 min) was observed with Marzyme than with MCE of Naturen (20.5 min) and Chy-max M (22.5 min). The results of the coagulation duration were explained by the stimulation of the activity of MCE of microbial origin, by the pH level of milk before coagulation (below pH 6.4). It was shown that modern MCEs of microbial origin could be recommended as a cost-effective replacement for more expensive rennet and recombinant chymosins in the production of soft and fresh cheeses.